Detecting Gamma-Band Responses to the Speech Envelope for the ICASSP 2024 Auditory EEG Decoding Signal Processing Grand Challenge - Thornton, Mike; Auernheimer, Jonas; Jehn, Constantin; Mandic, Danilo; Reichenbach, Tobias (2024 IEEE International Conference on Acoustics, Speech, and Signal Processing Workshops, ICASSPW 2024 - Proceedings, 2024)
The 2024 ICASSP Auditory EEG Signal Processing Grand Challenge concerns the decoding of electroencephalography (EEG) measurements taken from participants who listened to speech material. This work details our solution to the match-mismatch sub-task: given a short temporal segment of EEG recordings and several candidate speech segments, the task is to classify which of the speech segments was time-aligned with the EEG signals. We show that high-frequency gamma-band responses to the speech envelope can be detected with a high accuracy. By jointly assessing gamma-band responses and low-frequency envelope tracking, we develop a match-mismatch decoder which placed first in this task.
CRIS-Team Scopus Importer:2024-09-06
Keywords: deep learning; EEG decoding; speech

Estimation of the Neural Sources of the EEG-measured Speech-FFR using a Phenomenological Model of Auditory-nerve Fiber Responses - Auernheimer, Jonas; Reichenbach, Tobias (European Signal Processing Conference, 2024)
The frequency-following-response to continuous speech (speech-FFR) is a characteristic neural activity that emerges at the fundamental frequency of a speaker’s voice and can be measured by electroencephalography (EEG) and magnetoencephalography (MEG). Its spectrotemporal dynamics and neural sources encode important pitch information critical for reliable speech processing. EEG studies have found a peak latency of the speech-FFR at around 10 ms with putative subcortical origin while recent MEG studies identified additional cortical contributions to the speech-FFR driven by the carrier and the envelope modulations at higher frequencies. In this study, we examined the spatiotemporal dynamics of the speech-FFR at the fundamental frequency using linear modelling and inverse source localization. We found that the response mainly originates from subcortical sources with major contributions from the midbrain for the two implemented acoustic features, the fundamental waveform and higher frequency envelope modulations. Interestingly, the latter evoked some additional brainstem activity at latencies significantly later than the typical subcortical latency range. Our results confirm the subcortically-dominated nature of the EEG-measured speech-FFR while additional top-down modulation might be evident by recurring brainstem activity.
CRIS-Team Scopus Importer:2024-11-15
Keywords: EEG; Frequency-following-response (FFR); Fundamental frequency; Neural source localization; Speech-FFR